NCLEX-RN practice questions - Rinehart Gardner, Wilda (Exam cram., 2010)
1200+ Questions with Detailed Answers CD features 5 practice exams Covers exactly what you need to know to score higher on your NCLEX-RN® exam. Includes more than 1,250 sample test questions to help you determine whether you're ready to take the actual exam. Our popular Cram Sheet tear card helps you remember key concepts and facts. Use our innovative Quick-Check Answer Key System™ to quickly find answers as you work your way through the questions. Written by Leading Nursing Experts! Wilda Rinehart has R.N., B.S.N., M.S.N., F.N.C., and F.P.N.P. degrees. Her experience includes staff nurse in surgery, labor, and delivery; public-health nurse; and family-planning nurse practitioner. She also was an instructor of surgical and obstetrical nursing. Diann Sloan has R.N., B.S.N., M.S.N., F.N.C., as well as MS. Ed. and Ph.D. in Education degrees. She has worked as a staff nurse in surgical nursing, pediatrics, and neonatal intensive care and as a pediatric nurse clinician. She has also been an instructor of pediatric and psychiatric nursing. Clara Hurd has R.N., B.S.N., M.S.N., and G.N.C. degrees. She is currently serving as an item-writing consultant with Prentice Hall Publishing. She has 31 years of experience and has worked as a staff nurse in medical-surgical nursing and the surgical intensive care unit. Ms. Hurd has taught in associate and baccalaureate nursing programs. Score Higher on the NCLEX-RN® Exam! The CD features 5 practice exams, giving you an effective tool to assess your readiness for the NCLEX-RN® exam. Key features include: All 1,250 questions in this book are included on the CD, giving you yet another effective tool to assess your readiness for the NCLEX-RN® exam Multiple test modes, questions that simulate an actual RN exam, and detailed answer explanations Category: Test Preparation and Review Covers: Nursing NCLEX-RN® is a registered trademark of the National Council of State Boards of Nursing, Inc. (NCSBN), which does not sponsor or endorse this product.